A real time secured medical management system based on blockchain and internet of things. (February 2023) - Tiwari, Sharda; Dhanda, Namrata; Dev, Harsh
Abstract: Nowadays Electronic Health Care System is growing to a large extent. As data retrieve from IoT devices, that data is needed to store in a database as the different patients have different data. Due to a lack of intrinsic security safeguards, the Internet of Things is prone to privacy and security breaches. The information gathered from IoT devices is mostly saved in a database This data is very important for a particular patient. If this data is altered by any intruder, then the doctor cannot find the actual problem of the patient and also cannot give the patient proper treatment, as a result, it causes great harm to the patient. As a result, a security mechanism for the data contained in the database is required. Blockchain technology will help a lot in this situation. We make an IoT-based prototype that uses Blockchain technology to get rid of this anonymous data access, in the common word patient's data are private through this system.